DIVISION IN THE DINOFLAGELLATE GYRODINIUM COHNII (SCHILLER) : A New Type of Nuclear Reproduction - Kubai, Donna F. (The Rockefeller University Press, 1969)
Dinoflagellates are of interest because their chromosomes resemble the nucleoplasm of prokaryotes both chemically and ultrastructurally. We have studied nuclear division in the dinoflagellate Gyrodinium cohnii (Schiller), using cells obtained from cultures undergoing phasic growth. Electron micrographs of serial sections were used to prepare three-dimensional reconstructions of nuclei and chromosomes at various stages of nuclear division. During division, a complex process of invagination of the intact nuclear envelope takes place at one side of the nucleus and results in the formation of parallel cylindrical cytoplasmic channels through the nucleus. These invaginations contain bundles of microtubules, and each of the bundles comes to lie in the cytoplasm of a cylindrical channel. Nuclear constriction occurs perpendicular to these channels without displacement of the microtubules. There are no associations between chromosomes and the cytoplasmic microtubules. In dividing cells most chromosomes become V-shaped, and the apices of the V's make contact with the membrane surrounding cytoplasmic channels. It is proposed that the membrane surrounding cytoplasmic channels in the dividing nucleus may be involved in the separation of daughter chromosomes. Thus, dinoflagellates may resemble prokaryotes in the manner of genophore separation as well as in genophore chemistry and ultrastructure.